Motion corrected fetal body magnetic resonance imaging provides reliable 3D lung volumes in normal and abnormal fetuses. (15th March 2022) - Davidson, Joseph; Uus, Alena; Egloff, Alexia; van Poppel, Milou; Matthew, Jacqueline; Steinweg, Johannes; Deprez, Maria; Aertsen, Michael; Deprest, Jan; Rutherford, Mary
Abstract: Objectives: To calculate 3D‐segmented total lung volume (TLV) in fetuses with thoracic anomalies using deformable slice‐to‐volume registration (DSVR) with comparison to 2D‐manual segmentation. To establish a normogram of TLV calculated by DSVR in healthy control fetuses. Methods: A pilot study at a single regional fetal medicine referral centre included 16 magnetic resonance imaging (MRI) datasets of fetuses (22–32 weeks gestational age). Diagnosis was CDH ( n = 6), CPAM ( n = 2), and healthy controls ( n = 8). Deformable slice‐to‐volume registration was used for reconstruction of 3D isotropic (0.85 mm) volumes of the fetal body followed by semi‐automated lung segmentation. 3D TLV were compared to traditional 2D‐based volumetry. Abnormal cases referenced to a normogram produced from 100 normal fetuses whose TLV was calculated by DSVR only. Results: Deformable slice‐to‐volume registration‐derived TLV values have high correlation with the 2D‐based measurements but with a consistently lower volume; bias −1.44 cm 3 [95% limits: −2.6 to −0.3] with improved resolution to exclude hilar structures even in cases of motion corruption or very low lung volumes. Conclusions: Deformable slice‐to‐volume registration for fetal lung MRI aids analysis of motion corrupted scans and does not suffer from the interpolation error inherent to 2D‐segmentation. It increases information content of acquired data in terms of visualising organs in 3D space and quantification of volumes, which may improve counselling and surgical planning. Highlights: What's already known about this topic? Congenital diaphragmatic hernia (CDH) and congenital lung lesions (CLL) are prognosticated with ultrasound‐based measurements of the fetal lung in a single dimension; however true volumes may provide greater sensitivity for high risk cases. Current use of magnetic resonance imaging (MRI) to calculate fetal lung volumes is limited as two‐dimensional segmentation is labour intensive and risks interpolation and motion‐corruption errors. What does this study add? Three‐dimensional lung volumes can be computed from deformable slice‐to‐volume registration (DSVR) 3D reconstructions and highly correlate with traditional 2D‐derived volumes. DSVR‐derived volumes, however, should be more reliable owing to higher resolution and semi‐automated calculations that do not rely on interpolation between slices on motion‐corrupted stacks.